Clinical and functional outcome of surgery for posttraumatic cloacal deformity. (8th December 2021) - Picciariello, Arcangelo; Gallo, Gaetano; Sturiale, Alessandro; Litta, Francesco; De Simone, Veronica; Martines, Gennaro; Naldini, Gabriele; Ratto, Carlo; Trompetto, Mario; Rinaldi, Marcella
Abstract: Aim: Cloacal deformity is a disabling condition that severely affects a patient's quality of life. Surgery to repair cloacal deformity remains the mainstay of treatment. The aim of this study is to assess the clinical and functional outcome of patients treated for traumatic cloacal deformity by three different techniques. Method: A retrospective multicentre study was carried out using data from women operated on for cloacal deformity between 2015 and 2019. Demographic characteristics, the presence of urinary and/or faecal incontinence and manometric findings were collected. The main outcome measures were represented by St Mark's and Rockwood faecal incontinence quality of life scores. Results: Thirty eight women with a median age of 34 years [interquartile range (IQR) 31–39 years] were enrolled. Perineoplasty was performed in 23 patients by direct suture of the rectovaginal septum, in five using the X‐flap and in 10 by the Singapore flap. Median resting and squeezing pressures increased significantly from 28.15 (IQR 23–32.7) cmH2 O to 45 (IQR 31–60.7) cmH2 O ( p  = 0.0001) and from 47 (IQR 41.2–54.7) cmH2 O to 97.2 (IQR 80–118) cmH2 O ( p  = 0.0001), respectively. Maximum tolerable volume improved from 120 (IQR 90–137.5) ml to 137.5 (IQR 120–150) ml ( p  = 0.002). The St Mark's score decreased from 18 (IQR 14–20) to 4.5 (IQR 2–8) after 20 months ( p  = 0001). Sexual activity was confirmed by 16 patients preoperatively and by 27 postoperatively. A diverting stoma was performed in three patients after X‐flap perineoplasty and in 14 treated by direct closure. No significant differences were found pre‐ and postoperatively between the three groups. Conclusion: Regardless of the technique used, surgical repair significantly improves both clinical and functional outcomes irrespective of the presence of a covering stoma.